2021
DOI: 10.1177/17411432211002527
|View full text |Cite
|
Sign up to set email alerts
|

Vice-principals as leaders: Role ambiguity and role conflicts faced by vice-principals in Singapore

Abstract: This article examines what vice-principals in Singapore experience as constraints to their leadership practice, and how they deal with these constraints, cognisant that role misalignment for vice-principals presents barriers to schools achieving optimal effectiveness. This qualitative study seeks to hear the voices of vice-principals, to uncover the contextual richness of their experiences through interviews with 28 vice-principals. Coding involved a mix of codes from the literature and from the interviews, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This difference can be explained by the distinction between the principal's role definition and that of the vice-principal, as manifested in Israel (Arar and Oplatka, 2018) and other countries such as the United State, Canada (Mitchell et al ., 2017) and Singapore (Ho et al ., 2021). The principal is responsible for the functioning of the school and should be held accountable for its success towards the Ministry of Education and the local authority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference can be explained by the distinction between the principal's role definition and that of the vice-principal, as manifested in Israel (Arar and Oplatka, 2018) and other countries such as the United State, Canada (Mitchell et al ., 2017) and Singapore (Ho et al ., 2021). The principal is responsible for the functioning of the school and should be held accountable for its success towards the Ministry of Education and the local authority.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the principal is in constant contact with systems and people outside the school (Spillane and Sun, 2022). In contrast, the vice-principal engages in school management tasks at the intra-organizational level, such as responsibility for liaising with teachers and constructing the school hour system (Ho et al ., 2021; Arar and Oplatka, 2018). Thus, support from outside the school may be more available to the school principal while support from people within the school may be more available to the vice-principal.…”
Section: Discussionmentioning
confidence: 99%
“…The research results revealed that university faculty in business administration have high role expectations during low role ambiguity which facilitates role practices. In view of the ever-changing educational environment, university faculty in business management need to constantly pursue new knowledge, improve teaching, enrich the content, participate in study- or education-related workshops, and enhance their teaching and counseling abilities to reduce role ambiguity and achieve role expectation and role practice ( Ho et al, 2021 ). The administration unit should organize workshops according to the teachers who need to reduce the fear of negative reactions ( Tabancali and Su, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vice-principals often encounter role conflict and role ambiguity due to their intermediary position between the principal and teachers, leading to conflicting expectations (Mitchell et al ., 2017). As a result, they are seen as bridges between school management and staff, playing a crucial role in translating top management's objectives through effective communication and strategic implementation (Ho et al ., 2023). Despite the pivotal aspect of vice-principals being situated between the principal and teachers, this aspect has received limited scholarly attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vice-principals face a great deal of ambiguity in their role due to the lack of distinction between them and those below or above them in the organizational hierarchy (Ho et al ., 2023). The central authority and responsibility for all decisions regarding leadership and education in schools is in the hands of the school principal (Rintoul and Bishop, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%